1990
DOI: 10.1111/j.1460-2466.1990.tb02271.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Pornography: A Public Dilemma

Abstract: contrary to t v -wbofel strmzgly tbatpomograpby bas negadtne @f?~& especJalEy ott b m p~.~d r e l a t l O t l s betmen men and unnnen, atv m o r e o p p o s e d t o i t s~

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
1
15
0
3
Order By: Relevance
“…However, it seems that the relationship of this perceptual bias to attitudes in support of media restriction depends on the perceived harm and its interaction with other variables. Gender is one of the variables that earlier studies of pornography have found associated with stronger procensorship attitudes (Lee & Yang, 1996;Thompson et al, 1990). Social psychologists have found that women are more likely to support restrictions on pornography (Thompson et al, 1990) and also to be less likely to have had exposure to pornographic material (Dines et al, 1998;Lo et al, 1999;Wilson & Abelson, 1973).…”
Section: Ven-hwei Lo Anna Paddonmentioning
confidence: 91%
See 3 more Smart Citations
“…However, it seems that the relationship of this perceptual bias to attitudes in support of media restriction depends on the perceived harm and its interaction with other variables. Gender is one of the variables that earlier studies of pornography have found associated with stronger procensorship attitudes (Lee & Yang, 1996;Thompson et al, 1990). Social psychologists have found that women are more likely to support restrictions on pornography (Thompson et al, 1990) and also to be less likely to have had exposure to pornographic material (Dines et al, 1998;Lo et al, 1999;Wilson & Abelson, 1973).…”
Section: Ven-hwei Lo Anna Paddonmentioning
confidence: 91%
“…In their development of an Attitudinal Censorship Questionnaire, Hense and Wright (1992) found that although no gender differences were found on the General Censorship factor, females were more willing to censor pornography than were males. Thompson et al, (1990) found that women were more supportive than men of anti-pornography legislation. Lee and Yang (1996) also found that females were more likely than males to support censorship of sexual violence and sexually explicit materials on television.…”
Section: Ven-hwei Lo Anna Paddonmentioning
confidence: 96%
See 2 more Smart Citations
“…Os resultados dessas pesquisas mostram que homens e mulheres concordam com a proteção legal da publicação deste tipo de material, em defesa da liberdade de expressão. Também foi encontrado que os homens percebem mais efeitos positivos na utilização de pornografia para si mesmos e para os outros, mas que ambos os sexos concordam que a pornografia pode ter tanto efeitos positivos quanto efeitos negativos sobre os indiví-duos (Lottes, Weinberg, & Weller, 1993;Thompson, Chaffee, & Oshagan, 1990).…”
Section: Conceituação De Pornografia E Estudos Préviosunclassified